2017
DOI: 10.1017/s0144686x17001313
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and the body: one African perspective

Abstract: How do non-Western societies envisage the relationship between the body and ageing? The present work aimed to shed light on this question by exploring how adult men and women of different ages living in Dakar, Senegal, view their bodies. A quantitative methodology was selected, and this study was carried out on a sample of 1,000 dwellers of the Senegalese capital, aged 20 and older. This sample was constructed using the quota method in order to strive for representativeness. Results indicate that appearance wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…While their results were compatible with the idea of a (culturally) variable attractor age , such a distinct pattern was not observable in our sample from Nouna, questioning the cross-cultural validity of this concept in its original form. Furthermore, our findings support data by Macia et al (2019) who presented similar results, but without explicitly referring to the idea of an attractor age .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While their results were compatible with the idea of a (culturally) variable attractor age , such a distinct pattern was not observable in our sample from Nouna, questioning the cross-cultural validity of this concept in its original form. Furthermore, our findings support data by Macia et al (2019) who presented similar results, but without explicitly referring to the idea of an attractor age .…”
Section: Discussionsupporting
confidence: 92%
“…First, following previous studies conducted in Africa ( Macia et al, 2019 ) as well as meta-analytical work ( Pinquart & Wahl, 2021 ), we hypothesize that the absolute discrepancy between felt age and chronological age, across the span of chronological age, will be less pronounced than in the often-cited study by Rubin and Berntsen (2006) . Building on the idea of an attractor age , we likewise expect that this absolute discrepancy will be higher with increasing chronological age.…”
Section: Research Goalsmentioning
confidence: 87%
See 1 more Smart Citation
“…Correlatively, the social structures of the Ferlo seem to be characterized by their stability despite political and administrative changes: family and professional cycles are durable, elders are respected, and identities seem stable (e.g., Macia et al 2019). The close association between Fulani identity and pastoralism is a well-established anthropological fact (e.g., Botte et al 1999).…”
Section: Acceleration and Lifeworlds Of Sahelian Populations: The Cas...mentioning
confidence: 99%
“…However, research in African countries (and specifically in Nigeria for our purposes) is sparse compared to that focusing on Western and Eastern Asian populations [ 53 ]. Macia et al, [ 54 ] completed a study in Senegal which considered individual’s body image across the lifespan and reported that older Senegalese adults were less satisfied with their body than young adults. However, this study used only four questions adapted from a different study on Swedish adults [ 55 ], and reported a high degree of appearance satisfaction, even among the ‘less satisfied’ older age groups.…”
Section: Introductionmentioning
confidence: 99%